Effects of Prenatal Education on Maternal and Neonatal Outcomes in High risk Pregnant Women - Farzaneh Rahimi; Fariba Islami; Mohamad Mehdi Kahangi (پژوهان, 2018)
Background and Objective: Lack of awareness and the fear of women is one of the reasons for cesarean delivery and the occurrence of complications in maternal and neonatal period in our country. This study was conducted to investigate the effect of prenatal education on maternal and neonatal outcomes in high risk pregnant women. Materials and Methods: The present study was done as a randomized clinical trial on 150 high risk pregnant women was referred to Amiralmomenin Hospital in Shahreza, Iran in 2014. Samples were randomly assigned to control and intervention groups. The control group only received routine pregnancy care and case group received routine pregnancy care and prenatal education. After delivery, Maternal and neonatal outcomes  including  type of delivery , Apgar  index, weight and  height, head circumference, and  jaundice were assessed by using Chi-square and independent t-test. Results: Intervention and control groups did not significant in terms of demographic and obstetric variables (P>0/05). The results showed that a significant  difference between two groups in type of  delivery, height, weight and head circumference (P<0/001). However there was no significant difference  between the two groups  in Apgar scores and in jaundice (P>0.05). Conclusion: Raising awareness and education of pregnant women during pregnancy promote and improve the health of the baby and be a natural delivery. Therefore, it is suggested that prenatal education more widely used.